1998
DOI: 10.1136/bjo.82.9.1007
|View full text |Cite
|
Sign up to set email alerts
|

Extrafoveal photostress recovery test in glaucoma and idiopathic central serous chorioretinopathy

Abstract: Background/aims-A photostress recovery test was designed to diVerentiate macular diseases from optic nerve disorders, but recently an abnormal recovery time was reported in glaucoma. The purpose of this study was to search for the diVerence in abnormality of the photostress recovery test between glaucoma and idiopathic central serous chorioretinopathy (ICSC). Methods-This study involved 21 normal subjects, 14 patients, with ICSC and 10 patients with primary open angle glaucoma (POAG). A scanning laser ophthalm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 27 publications
(14 reference statements)
0
17
0
Order By: Relevance
“…The earliest studied was central serous retinopathy (CSR). 19 It was initially felt that an increase in recovery time was unique to this condition, as only limited testing on patients with diabetic retinopathy, 23 cystoid macular edema, 45 and AMD 3 had been done. With further investigation, the presence of diabetic macular edema (retinal thickening at or within one disc diameter of center) has been associated with prolonged photostress recovery times.…”
Section: Discussionmentioning
confidence: 99%
“…The earliest studied was central serous retinopathy (CSR). 19 It was initially felt that an increase in recovery time was unique to this condition, as only limited testing on patients with diabetic retinopathy, 23 cystoid macular edema, 45 and AMD 3 had been done. With further investigation, the presence of diabetic macular edema (retinal thickening at or within one disc diameter of center) has been associated with prolonged photostress recovery times.…”
Section: Discussionmentioning
confidence: 99%
“…66 79 Most clinical photostress tests measure how long it takes for visual sensitivity to recover after bright light exposure. Vision is the most common test end point, 39 but pupillary 80 and visually evoked 81 82 recovery times can also be measured. Photostress luminances and exposure durations vary between protocols.…”
Section: Testing Glare and Photostressmentioning
confidence: 99%
“…It has previously been shown that PSRT is adversely affected by conditions affecting the macula, including central serous retinopathy, 39 age-related macular degeneration, 25 and diabetic maculopathy. [25][26][27] Disruption of the retinal pigment epithelium-retina relationship, because of serous retinal detachment or macular edema for example, has been shown to be an important factor in the prolongation of PSRT in such macular disease.…”
Section: Discussionmentioning
confidence: 99%